Perubahan warna bahan mahkota tiruan sementara direk setelah perendaman gula merah pada teh susu (Laporan Penelitian) - Nathania Immanuela Tanos; James Handojo (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Brown sugar is a food ingredient that is often used in food and beverages that we consume daily. Brown sugar can cause discoloration in dental restoration material. Purpose: To determine the discoloration of temporary crown direct technique bis-acryl composite resin after soaking in milk tea that contains brown sugar. Research Methods: Method of this research is laboratory experimental. Total of 10 samples were divided into 2 groups, 5 samples of the first group were immersed in milk tea, while 5 samples of the second group were immersed in milk tea that contains brown sugar with duration of 10 minutes each day for 7 days. The discoloration of the material were tested using VITA Easyshade V. Data results from the color test were processed statistically by T Test . Results: From this study, it can be said that there were no significant color change in all samples because the p value of all the color indicators (ΔE, ΔL, ΔC, and ΔH) > 0.05. Conclusion: There was no significant color change in of temporary crown direct technique bis-acryl composite resin after immersed in brown sugar milk tea.